Preparing non‐government organization workers to conduct health checks for people with serious mental illness in regional Australia. Issue 5 (9th June 2016) - Jones, Martin; Kruger, Mellissa; Walsh, Sandra M.
Accessible summary: What is known on the subject?: People diagnosed with schizophrenia or bipolar disorder have a life expectancy 10–15 years less than the general population. In rural and remote Australia, there is a shortage of health care professionals to provide physical health care for people living with a serious mental illness (SMI). A large proportion of the care for people living with a SMI is provided by non‐government organizations (NGOs), often employing workers without formal qualifications. There has been minimal research regarding the experiences of NGO workers who have been trained to complete health checks to help people living with SMI to access primary care services. What this paper adds to existing knowledge?: This is the first study to examine the experiences of preparing NGO workers to use the health improvement profile (HIP) to support the physical health of people with SMI. It builds on previous studies that examined the use of the HIP by trained/qualified staff. What are the implications for practice?: This study highlights that NGO employees may have an important role in helping people with a SMI to address their physical health. Engaging lay workers to use the HIP increases their awareness of the importance of providing good physical health care for people with SMI. The use of a tool, such as the HIP, prepares NGO workers to support the physical health needs and enables them to describe meaningful improvements in the health of people with a SMI. Abstract: Background: The life expectancy of people living with a serious mental illness (SMI) is up to 10–15 years less than the general population. They experience difficulties in accessing timely and appropriate physical health care. People with SMI living in regional Australia experience additional barriers to accessing services. This is in part due to the difficulties associated with recruiting and retaining health professionals in regional Australia. Aim: To explore the regional non‐government organization (NGO) workforce views of using a physical health care check list – the health improvement profile (HIP) – with people with a SMI. Gain insights into the workers' experiences of using the HIP. Understand which aspects of the HIP workers perceived as being most and least helpful. Learn how the HIP and the training program could be modified to better support its application in regional Australia. Method: A focus group using a semi‐structured interview was conducted with seven NGO employees who had been trained to use the HIP and subsequently used the HIP in their everyday work with patients. A mental health nurse (MHN) and a Psychology graduate working for the University of South Australia Department of Rural Health conducted the focus group. Results: Using thematic analysis, the focus group discussion generated four main themes: taking control; accessing services; guiding my conversation; and working with others. The overall meta‐theme was that lay workers can work effectively to address physical health problems in SMI patients. Conclusion: Our observations highlight the important role lay workers in regional Australia have in helping people with SMI to address their physical health needs. They have an opportunity to extend their role in parts of the world where it is difficult to recruit MHNs.